Desain Front End Aplikasi Toko Sepatu Dixstore10 Menggunakan Metode Design Thinking - Wahyu Aziz Ramadhani; Bayu Priyatna; Elfina Novalia (Lembaga Pengembangan Kinerja Dosen, 2025)
The objective of this study is to formulate the design of Dixstore10's front-end application interface by applying the design thinking method, which focuses on user needs. Dixstore10 is a local shoe store that supports local products and offers quality shoes to different groups. In this study, the design thinking approach is implemented in five main steps, which form the core of this method. In the